Plasmodium Falciparum-infected Erythrocytes: A Mutational Analysis of Cytoadherence via Murine Thrombomodulin - Rabhi-Sabile, Samia; Steiner-Mosonyi, Marta; Pollefeyt, Saskia; Collen, Desiré; Pouvelle, B.; Gysin, Jurg; Boffa, Marie-Claire; Conway, Edward M. (Thrombosis and Haemostasis, 1999)
The pathophysiologic events leading to organ damage in Plasmo-dium falciparum malaria infections involve adhesion and sequestration of parasite-infected erythrocytes (PRBC) to the vascular endothelium and syncytiotrophoblast. Several potential receptors to which the PRBCs may bind have recently been identified, one of which is thrombomodulin (TM). TM has been implicated particularly in mediating sequestration of P. falciparum-infected erythrocytes in the placenta and brain, two sites of disease associated with high morbidity. In order to establish that binding of parasite-infected red blood cells to TM is dependent on its containing chondroitin-4-sulfate (CSA), we have mutated the CSA-attachment site of murine TM, and expressed this mutant form (TMser-gly) in COS-7 cells. In cytoadhesion assays, we demonstrate that, in contrast to wild-type TM which contains CSA and supports the adhesion of 1466 PRBCs/mm2, TMser-gly does not contain CSA and adhesion of PRBCs to those cells expressing TMser-gly is entirely abrogated (200 PRBCs/mm2). These studies further confirm that the CSA of TM may play a role in the pathophysiology of malaria by providing a binding site for PRBCs.